Evidence of multiple mechanisms of alphacypermethrin and deltamethrin resistance in ticks Rhipicephalus microplus in Benin, West Africa - YESSINOU, R. ERIC; AKPO, YAO; SIDICK, ABOUBAKAR; ADOLIGBE, Camus Mahougnon; YOUSSAO ABDOU KARIM, ISSAKA; AKOGBETO, CODJO MARTIN; FAROUGOU, SOUAÏBOU (My University, 2018)
Ticks are obligate haematophagous arthropods, causing heavy losses in affected livestock. The objective of this study is to investigate phenotypic and genotypic resistance in Rhipicephalus microplus populations from Benin. Engorged female adult ticks were collected from cattle in two districts of Benin. Bioassays, biochemical and molecular tests were carried out on these ticks to determine the phenotypic, enzymatic and genetic status of resistance. Results of bioassays showed high resistance factors (RF > 41). The molecular tests showing the presence of the domain II mutation and absence of the domain III mutation in the voltage-gated sodium channel gene. Biochemical tests showed increased activity of esterases, multifunction oxidases and glutathione transferases in resistant samples. Genotyping the samples showed high levels of heterozygous genotypes (73.36% and 63.30%) as compared to homozygous susceptible and resistant genotypes (23.3% and 10%) respective at Samiondji and Betecoucou. A correlation between phenotype resistance and presence of the domain II mutation at the voltage gated sodium channel gene was observed suggesting that this could be associated with resistance. Target site mutation and metabolic detoxification are mechanisms of resistance to pyrethroids in R. microplus tick populations from Benin.
Keywords: Enzymatic; Genetic mutation; Esterases; Oxidases; Glutathion-S-transferases